Monadic Fragments of Intuitionistic Control Logic - Glenszczyk, Anna (Bulletin of the Section of Logic, 2016)
We investigate monadic fragments of Intuitionistic Control Logic (ICL), which is obtained from Intuitionistic Propositional Logic (IPL) by extending language of IPL by a constant distinct from intuitionistic constants. In particular we present the complete description of purely negational fragment and show that most of monadic fragments are finite.